Delegitimation of Komnas Perempuan's Discourse on Sexual Violence in the Ferdy's Sambo Case - Nur Imroatus Sholikhah (BPSDMP KOMNFO Yogyakarta, Kementerian Komunikasi dan Informatika, 2023)
This article examines the phenomenon of netizens’ negative responses towards the statement by Komnas Perempuan regarding the alleged sexual violence experienced by Ferdy Sambo's wife, as a form of delegitimation. Legitimation is built by discursive practice, and hence can be delegitimated by mechanisms of opposition. Delegitimation is carried out through three components of discursive legitimation, namely: (i) authority, (ii) rationality and (iii) symbolic. As a research method, a case study of citizens’ Twitter posts (tweets) from 1-10 September 2022 were analyzed using Intelligent Socio Analytic (ISA), a social media big data extraction tool. The results show in terms of authority, discursive delegitimation is carried out by positioning Komnas Perempuan to be supporting the narrative of the Police. In the aspect of rationality, Komnas Perempuan's discourse is seen as protecting the perpetrators of the murder instead of siding with the victim’s families. As for symbolic narratives, Komnas Perempuan is equated with other institutions that can be bribed and are weak in the face of power. In the digital era, discursive delegitimation can strengthen or weaken the digital authority of the public.